2021
DOI: 10.3390/plants10040753
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Potato Virus Y (PVY) Using High-Throughput Sequencing: Constraints on Full Genome Reconstructions Imposed by Mixed Infection Involving Recombinant PVY Strains

Abstract: In recent years, high throughput sequencing (HTS) has brought new possibilities to the study of the diversity and complexity of plant viromes. Mixed infection of a single plant with several viruses is frequently observed in such studies. We analyzed the virome of 10 tomato and sweet pepper samples from Slovakia, all showing the presence of potato virus Y (PVY) infection. Most datasets allow the determination of the nearly complete sequence of a single-variant PVY genome, belonging to one of the PVY recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…RDP5 analysis of the P1 regions of three pepper PVY isolates (DB57, DB59 and KB4) together with three O, three N and three C phylogroup homologous sequences chosen at random from the alignment of 634 sequences (see below) indicated that the N-terminal portion of the pepper P1 genes have an O phylogroup region with a cross-over point around 310 nts with an average P-value (eight methods) of having occurred by chance of 1.20x10 -21 (Figure 3). This con rms that they are from phylogroup R1, and, in particular, from its N-Wi cluster as reported by Glasa et al, (2021).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…RDP5 analysis of the P1 regions of three pepper PVY isolates (DB57, DB59 and KB4) together with three O, three N and three C phylogroup homologous sequences chosen at random from the alignment of 634 sequences (see below) indicated that the N-terminal portion of the pepper P1 genes have an O phylogroup region with a cross-over point around 310 nts with an average P-value (eight methods) of having occurred by chance of 1.20x10 -21 (Figure 3). This con rms that they are from phylogroup R1, and, in particular, from its N-Wi cluster as reported by Glasa et al, (2021).…”
Section: Resultssupporting
confidence: 85%
“…These have a major O parent and a minor N group minor parent of their 5' terminal region, but have a 3' terminal region that was either from an O lineage parent (R1) or an N lineage parent (R2). Glasa et al (2021) have now also shown that both recombinant lineages have major sublineages de ned by the 5' termini of their P1 regions, which is either N-lineage (pathogroups N:O and NTNa) or N lineage with a 5' O lineage cap of 310 nts (pathogroups N-Wi, NTNb). Our three pepper PVY recombinant isolates have the O+N 5' terminal O region con rming that they are from the N-Wi pathogroup, which is part of the R1 phylogroup.…”
Section: Phylogroup Assignmentmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, in previous works analyzing viral populations in Slovakia, mixed infections involving different variants of the same virus species were noted, both for annual (PVY/tomato [45]) or perennial hosts (CVA/cherry [46]; GRSPaV/grapevine [47]). In our experiments, only a single-variant CMV population was detected in each sample (as supported by analysis of de novo contig assemblies and visual inspection of reads), enabling the accurate reconstruction of nearly full-length CMV genomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in next-generation sequencing (NGS) have led to the unprecedented generation of genomic and transcriptome data that are now available in public data depositories. These data have brought new possibilities to identify coinfecting known and novel virus genomes [25,26]. Therefore, we screened selected genomic datasets from three projects that report sequencing data for cocoa accessions from Brazil, Puerto Rico or Trinidad with the aim of detecting the Trinidad viruses.…”
Section: Identification Of Cammv and Cyvbv Viruses In Genomic Sequencing Datasets Of Cocoamentioning
confidence: 99%